(untitled) - Piggott, Juliet (Feltham (England), 1969)
Japan is a country rich in myths, legends and folk tales. Many stories are still told of actual historical characters. It is not easy to set a date for the beginning of the historical period, and the mighty deeds of such men as Tametomo and Yoshitsune have been magnified in both number and renown. But such stories of valour and strife are only one side of japanese mythology.
Keywords: Mythology, japanese